OPTIMAL CONDITIONS FOR EXTRACTION PHENOLIC COMPOUNDS AND FLAVONOIDS FROM MILLET BRAN AND STUDYING SOME OF THEIR BIOLOGICAL ACTIVITY - Mariem M. A.AL-Abas; Jassem. M. Nasser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The aim of this research is to determine the optimal conditions for extracting phenols and flavonoids from the bran of Iraqi proso millet and Ukrainian foxtail millet, whole and defatted, and studying some of their biological characteristics. Petroleum ether, methyl alcohol (60% and 80%), distilled water, and ethyl alcohol at concentrations of 60, 80, 90, and 99% were used as extraction solutions. The flavonoid content was estimated using the Rutin standard curve, and the phenolic content was determined using the Folin-Ciocateau method based on the gallic acid standard curve. The results showed that the concentration of phenolic compounds and flavonoids in proso millet bran extracts were (770.56, 865.38, 1059.94, 883.16, 722.17, 726.12, 587.79, 400.69) µg/g and (188.26, 196.26, 353.60, 671.38, 96.94, 93.60, 117.60, 300.60) µg /g, respectively, and in Ukrainian millet bran extracts (889.08, 1034.80, 1182.00, 1331.17, 1008.19, 990.42, 592.85, 581.43) µg /g and (302.94, 484.26, 758.94, 940.32, 188.26, 97.60, 217.60, 554.94) µg/g respectively. The highest phenolic and flavonoids compounds concentrations were achieved when ethyl alcohol (99%) as extraction solution was used for Ukrainian millet. Therefore, this treatment was adopted in conducting the free radical scavenging test, at different concentrations (0.125, 0.250, 0.500, 0.750, 0.800) mg/ml, as RSA were (24.68, 40.18, 67.56, 81.98, 89.55%), respectively, compared to ascorbic acid at the same concentrations, which were (40.14, 57.34, 73.46, 89.93, 99.55%).